Cloning and functional characterization of two peptidoglycan recognition protein isoforms (PGRP-LC) in Bactrocera dorsalis (Diptera: Tephritidae) - Dong WEI; Zhe WANG; Hui-qian XU; Jin-zhi NIU; Jin-jun WANG (Journal of Integrative Agriculture, 2020)
The innate immune system of insects is the front line of self-defense against pathogen invasion. Peptidoglycan recognition proteins (PGRPs) are important components and play key roles in insect immune systems by recognizing peptidoglycan (PGN) in bacterial cell walls. We characterized two isoforms of the PGRP-LC gene, BdPGRP-LCa and BdPGRP-LCb, from Bactrocera dorsalis (Hendel), an important fruit and vegetable pest worldwide. These two isoforms contain an open reading frames of 1 668 bp and 1 731 bp, encoding a protein of 555 and 576 amino acids, respectively. Quantitative real-time PCR results showed that both transcripts were prominently expressed in midgut and fat body of B. dorsalis adult. Inoculation of pathogens showed that both isoforms actively responded to Escherichia coli PGN. We also observed a light response to Staphylococcus aureus PGN. Upon Beauveria bassiana inoculation, the expression of BdPGRP-LCa was enhanced, but the expression of BdPGRP-LCb was suppressed. Suppression of both transcripts by RNA interference led to increased mortality of flies challenged by E. coli, indicating that the two isoforms are involved in sensing Gram-negative bacterial infections.